Additional limitations when searching for images on stereopairs along epipolar lines - V. P. Pivovarov; A. V. Zubar (Омский научный вестник)
The article regards the problem solution of finding additional restrictions on the area of the image searches according to the stereoscopic pairs set by the epipolar line. The feature of the given approach is a possibility of finding the restrictions based on mathematical dependences, which do not require the finding of the fundamental matrix and preliminary processing of images.